Paper 34: Kinematic Analysis of Lateral Meniscus Oblique Radial Tears in Anterior Cruciate Ligament Reconstructed Knees: Untreated versus Repair versus Partial Meniscectomy. Issue 7 (30th July 2022) - Bezold, Will; Cook, Cristi; Krych, Aaron; Stuart, Michael; Wijdicks, Coen; Cook, James; Smith, Patrick
Objectives: Objectives: Previous analyses have characterized the incidence of lateral meniscus oblique radial tears (LMORT) commonly seen with ACL tears, and their impact on joint and meniscus stability in the presence of ACL deficiency. Purpose: To determine the clinically relevant kinematics associated with LMORT lesions untreated versus arthroscopic repair versus partial meniscectomy in combination with anterior cruciate ligament reconstruction (ACLR). Methods: Sixteen cadaver knees underwent robotic testing for anterior drawer (AD) and pivot shift (PS) simulations at multiple knee flexion angles in intact and ACL-deficient states, followed by sequential testing of arthroscopic ACL reconstruction (ACLR), creation of a LMORT 3 lesion, LMORT 3 repair, and partial meniscectomy (PM; n=8). The same testing sequence was performed for LMORT 4 lesions (n=8). Changes (Δ ) from the intact state for anterior translation, internal rotation, and valgus displacements, as well as ultrasoundographic measurements of meniscal extrusion, were measured and comparatively analyzed. Results: ACLR restored kinematics in ACL-deficient knees to intact levels for all metrics tested. For AD, ACLR + LMORT3 tear and PM resulted in significantly greater anterior translation (0.8-2.1 mm differences) compared to ACL-intact at all angles ( P < 0.05) and compared to ACLR at 60 o and 90 o ( P < 0.014). For PS, ACLR + LMORT3 tear had significantly more anterior translation (1-1.4 mm differences) at 15 o than intact knees (P=0.041), and at 0 o and 15 o for PM ( P < 0.03). ACLR + LMORT4 tear and PM resulted in significantly greater anterior translation (0.9-2.3 mm differences) for AD ( P < 0.04) and PS testing ( P < 0.05) compared to intact and ACLR knees at all angles tested. ACLR+LMORT 3 repair and ACLR+LMORT4 repair restored kinematics to ACLR and intact levels at all angles tested. ACLR + LMORT3 tear ( P < 0.008) and both LMORT4 tear and PM ( P < 0.05) resulted in increased meniscal extrusion (1.8-11 mm differences) compared to intact and ACLR statuses at all tested angles for AD and PS while repairs restored meniscus stability to ACLR and intact levels. Conclusions: Untreated LMORT 3 and 4 tears increased anterior translation, pivot shift, and meniscus extrusion even after ACLR, while partial meniscectomy further exacerbated these detrimental effects. In contrast, arthroscopic side-to-side repair of LMORT lesions effectively restored measured knee kinematics. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/6bf43418-abf1-49bd-b78b-cc0c501a2da0/1/AOSSM_Abstract_Images.docx UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/b0f0bf53-a166-4cec-bf73-176ea452b905/1/AOSSM_Abstract_CHART.docx